The Oxford handbook of the economics of poverty - Jefferson, Philip N. (Oxford : Oxford University Press, 2012)
This handbook examines poverty measurement, anti-poverty policy and programs, and poverty theory from the perspective of economics. It is written in a highly accessible style that encourages critical thinking about poverty. What's known about the sources of poverty and its alleviation are summarized and conventional thinking about poverty is challenged.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Poverty; Poor; Labor market